Variabilidade fluviométrica do Rio Tapajós em Santarém (Pará) - ÁVILA, Pâmela Lorena Ribeiro (2019)
This paper presents a contribution to studies of climate modeling with emphasis on seasonal rainfall variability in the state of Pará, during the summer and autumn (DJF and MAM). Based on the results of simulations of regional RegCM4 for El Niño years (1982/83) and La Niña (1988/89) using the field at high spatial resolution (40 km) and two different convection schemes (Grell and MIT), was investigated the performance of the model to simulate the regional distribution of seasonal rainfall in the state of Pará, with reference to a new set of observational data compiled with information from three rainfall stations. The quantitative analysis showed that the RegCM4 presents systematic errors, especially those related to an underestimation of rain in three grades (G1, G2, G3) for the years of El Niño and La Niña are representative only in small areas in the southeastern state in summer period for the Grell scheme, and was more representative of the grid G2 for the year of El Niño in the MIT scheme. Moreover, using the technique of composition, was also investigated in the performance of RegCM4 reproduce the spatial patterns of anomalous seasonal rainfall in association with ENSO episodes and phases of the thermal gradient over the Atlantic intertropical. The results showed that the model represented realistically and spatial patterns of rainfall anomalies above (below) of normal in much of the eastern Amazon, during the known favorable scenarios, ie, La Niña and gradient SSTa South Atlantic (unfavorable, ie, El Niño and gradient SSTa North Atlantic).